Mobile phone Icons recognition and cultural aspects - Ghayas, S. (Institute of Electrical and Electronics Engineers Inc., 2014)
There is a rapid growth in the development of mobile phone applications which are widely used around the globe. Different cultures may affect the usage of such applications; there is a need to explore the cultural differences in this context. In order to study such differences, those icons which interpretability might be affected by culture differences are taken into consideration and hypothesized. Two groups of ten subjects (twenty in total) from two different countries i.e. Malaysia and Estonia participated in the study. The factors considered in the study were navigation time, working with menu icons, and recognition test. The results indicated that Malaysian subjects performed well while interpreting the third generation of icons which were operating system provided icons. On the other hand, Estonian subjects were not much familiar with modern icons. There was no difference found in the both groups to interpret the most familiar icons. The results reveal that there are possible cultural differences on icons interpretability based on their levels of abstraction. Â© 2014 IEEE.